Enthesis Repair: Challenges and Opportunities for Effective Tendon-to-Bone Healing. (15th August 2018) - Derwin, Kathleen A.; Galatz, Leesa M.; Ratcliffe, Anthony; Thomopoulos, Stavros
Abstract : Abstract: On May 22, 2017, the National Institutes of Health (NIH)/National Institute of Arthritis and Musculoskeletal and Skin Diseases (NIAMS) hosted a roundtable on "Innovative Treatments for Enthesis Repair." A summary of the roundtable discussion, as well as a list of the extramural participants, can be found at https://www.niams.nih.gov/about/meetings-events/roundtables/roundtable-innovative-treatments-enthesis-repair. This paper reviews the challenges and opportunities for developing effective treatment strategies for enthesis repair that were identified at the roundtable discussion.